Knowledge works : the handbook of practical ways to identify and solve common organizational problems for better performance - Winkelen, Christine van.; McKenzie, Jane. (Chichester, West Sussex, U.K. : Wiley, 2011)
Knowledge Works is a handbook full of ideas to help you draw on people's knowledge to keep ideas fresh, reduce waste, and build competence and capability. You can either dip into it according to your needs, or work through it in a more systematic way to create a plan to improve your organization's performance. "Knowledge Works is a very practical book that provides proven solutions for important knowledge-related problems in organizations including: how to convince managers that knowledge is important, how to create a knowledge-sharing culture, and how to improve the quality of conversations.
Cover; Praise for Knowledge Works; Title page; Copyright page; INTRODUCTION; Section I: Establish strategic priorities; What do we mean by strategic priorities?; How do you establish them?; Key questions to ask yourself; Chapter 1 IDENTIFYING VALUABLE KNOWLEDGE; Snapshot; Why this matters; What this means for your organization; Creating an action plan; Real life stories; Top tips; The research and the team involved; Final reflections from the research; Chapter 2 MAKING A COMPREHENSIVE ASSESSMENT OF KNOWLEDGE FLOWS; Snapshot; Why this matters; What this means for your organization.
Title from title screen.
Includes bibliographical references and index.
Keywords: Knowledge management; Organizational learning; Problem solving; BUSINESS & ECONOMICS -- Information Management; BUSINESS & ECONOMICS -- Knowledge Capital; Knowledge management; Organizational learning; Problem solving; Electronic books